SISTEM INFORMASI MANJEMEN PENGGAJIAN PNS PADA PEMERINTAH KABUPATEN KARANGASEM - I Made Panca Setiawan; Ni Ketut Dewi Irwanti (Journal of Applied Management Studies, 2021)
The purpose of this study was to determine the system and procedure for issuing a list of civil servants salary with application-based payroll management, namely the Payroll Management Information System, and also the benefits of paying civil servants compensation. By implementing payroll management based on information systems, of course it will make the organization in this case the Karangasem Regency Government make a breakthrough so that the salaries of civil servants in the thousands can be paid on time every month without any problems. The payroll management information system prevents errors when calculating the issuance of the payroll, does not require a lot of human resources, time and energy is maintained especially during the current covid'19 pandemic, the realization of data accuracy and personnel and financial information that comes out of SIMGAJI, the availability of a personnel and financial database for each civil servant, as well as being faster in submitting a report on the realization of salary payments to the Ministry of Finance of the Republic of Indonesia in Jakarta through an integrated application as the basis for distributing the General Allocation Fund (DAU) to the Regional Government regarding how much the central government has prepared for the budget. Pay civil servants salaries every month in the area. The process of issuing a list of PNS salaries to the Karangasem Regency Government is carried out from the setting, input, process, to the results/outputs in the form of a list of PNS salaries which will be used as the basis for paying civil servants salaries every month.